THE UNHEALTHY DELIGHTS: ONLINE GAMES – DOES PERSONALITY TRAITS AND NEEDS SATISFACTION PLAYS A ROLE? - Liesera, Novita; Tiatri, Sri; Widiastuti, Niken (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2019)
Playing too many online games could harm the player both physically and mentally. Online game engagement is a generic indicator of one’s involvement in online game playing (Brockmyer, Fox, Curtiss, McBroom, Burkhart, & Pidruzny, 2009). The previous study found that three out of five traits from the Five Factor Model correlates with psychological needs fulfillment (Teng, 2009). Online games serve as a mean to fulfill these psychological needs (Przybylski, Rigby, & Ryan, 2010). This study attempts to understand the correlation between personality traits and the online game engagement of adolescents in Jakarta with basic psychological needs satisfaction as a mediator. The participants of this study are adolescent gamers age between 15 to 18 years (n = 333). Quantitative methods and questionnaires are used to gather information from participants. Regression result shows that basic psychological needs satisfaction mediates personality traits and online game engagement. Out of five traits, basic psychological needs satisfaction only mediates for conscientiousness (r2 = 0.050, p < 0.01) and neuroticism (r2 = 0.051, p < 0.01).